Pengawasan Pendidikan Islam di Pondok Pesantren Bustanul Mansuriyah: Analisis Kualitas dan Efisiensi - Aflah Az Zahra, Aurelia; Tarifin, Ahmad; Tri Lestari, Sofianti; Umam Nawawi, Sahil Rosikhul; Fitrianingsih, Sri Eka (La-Tahzan: Jurnal Pendidikan Islam, 2024)
Islamic boarding schools have an important role as broadcasters of Islamic preaching in Indonesia. The existence of this Islamic boarding school requires good supervision in its management. The aim of this research is to describe the implementation of supervision and the extent to which supervision has been carried out effectively and efficiently at the Bustanul Mansuriyah Islamic boarding school in Rowolaku, Kajen District, Pekalongan Regency. The urgency of this research is to evaluate the effectiveness of the supervision methods applied to improve the quality of education and to minimize potential problems in supervision in Islamic boarding schools. The approach used in this research is a qualitative approach. The results of the research show that supervision of Islamic education at the Bustanul Mansuriyah Islamic boarding school is quite effective, but from a structural perspective there is no supervision within the boarding school. Based on the results of this research, supervision generally starts with each student who has the responsibility to supervise each other. There are no special methods available in educational institutions, they still rely on collective and communicative supervision. Where everyone is involved in security and supervision. In this case, it is then communicated through coordination channels within the management structure of the Bustanul Mansuriyah Islamic boarding school. The involvement of all parties in the implementation of supervision at the Bustanul Mansuriyah Islamic boarding school, as well as the implementation of supervision that is guiding and flexible, is the key to the success of implementing effective and efficient supervision at the Bustanul Mansuriyah Islamic boarding school.